An Angle Compared Index with Hybrid of Changes in the Ratio and Amplitude for Quantitative Evaluation of Disease Risk, Biological Function, and Biomarker Efficacy. (5th August 2019) - Xiaojun, Jin; Hui, Liu
Abstract : Objective . The purpose of this study was to describe variations of different cardinal frequency by using angle compared index (ACI). Methods . The basic principle of the analysis model is to comprehensively consider changes in both the ratio and absolute value as follows: ACI = arctanP d ⁎ (1-Pc) / [Pc⁎ (1-P d ) ] + arctan (Pd - Pc) - 45, where Pd represent percentage of disease occurrence in disease group and Pc represent that in control group. The range of ACI was (0 90). Thus, ACIs from different cardinal frequency are comparable. Results . When biomarkers with similar ratio value, absolute value, or ACI but different positive frequencies were combined, although three indexes (ratio value, absolute value, or ACI) increased after two single biomarkers were combined, only ACI increased with similar amplitudes after two single biomarkers with the same ACI at different positive frequencies were combined. Conclusion . The ACI provides a better understanding power of biomarker and may be a relatively good index for evaluating the complex events represented by different cardinal frequency from new systems.